2018
DOI: 10.1093/toxsci/kfy283
|View full text |Cite
|
Sign up to set email alerts
|

All-trans Retinoic Acid Disrupts Development in Ex Vivo Cultured Fetal Rat Testes. II: Modulation of Mono-(2-ethylhexyl) Phthalate Toxicity

Abstract: Humans are universally exposed to low levels of phthalate esters (phthalates), which are used to plasticize polyvinyl chloride. Phthalates exert adverse effects on the development of seminiferous cords in the fetal testis through unknown toxicity pathways. To investigate the hypothesis that phthalates alter seminiferous cord development by disrupting retinoic acid (RA) signaling in the fetal testis, gestational day 15 fetal rat testes were exposed for 1-3 days to 10 À6 M all-trans retinoic acid (ATRA) alone or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 86 publications
1
13
0
Order By: Relevance
“…E2f1-null testes showed a progressive loss of spermatogonia, but the mechanism causing this germ cell loss is unknown. Wnt signaling is activated in stress situations causing cell death; in particular, Wnt4 is upregulated after testicular exposure to genotoxic agents, phthalates and retinoic acid (Pecína-Šlaus, 2010;Spade et al, 2019;Xu et al, 2014). Ectopic activation of WNT4/CTNNB1 signaling in Sertoli cells downregulates SSC activity (Boyer et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…E2f1-null testes showed a progressive loss of spermatogonia, but the mechanism causing this germ cell loss is unknown. Wnt signaling is activated in stress situations causing cell death; in particular, Wnt4 is upregulated after testicular exposure to genotoxic agents, phthalates and retinoic acid (Pecína-Šlaus, 2010;Spade et al, 2019;Xu et al, 2014). Ectopic activation of WNT4/CTNNB1 signaling in Sertoli cells downregulates SSC activity (Boyer et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The RSP works in several developmental processes, including axial skeleton development, heart outflow tract development, and nervous system development (Ishioka et al, 2011; Kaiser et al, 2003; Stefanovic & Zaffran, 2017). There is evidence demonstrating the relationship between RSP and PAEs (Chen & Reese, 2013, 2016; Spade, Hall, Wortzel, Reyes, & Boekelheide, 2019). Therefore, we hypothesized that developmental defects from paternal DBP exposure may be related to epigenetic modification involving DNA chemical modification in early embryonic development, especially in some important genes in the RSP.…”
Section: Discussionmentioning
confidence: 99%
“…Control of RAR signaling is critical for the development and function of the testis. We have shown that phthalates interact with exogenous retinoic acid in the fetal testis, modulating the effects of retinoic acid on cord development (Spade et al 2019b). This hypothesis is consistent with the effects of phthalates on the regulation of genes and proteins involved in the specification of the supporting cell lineage to granulosa or Sertoli-like phenotypes (Wang et al 2015, Spade et al 2019a.…”
Section: Possible Molecular Targetsmentioning
confidence: 99%
“…In fact, many phthalates are predicted in silico to bind to all three human PPAR isoforms. Further, interactions between PPARs and other nuclear receptors, such as RARs, could explain a portion of the phthalate toxicity mechanism (Dufour et al 2003, Spade et al 2019b. Beyond activation or inhibition of PPARs or crosstalk between PPARs and other nuclear receptors, at least two additional MIEs have been proposed in phthalate AOPs, both primarily related to testosterone.…”
Section: Resolving Questions About Phthalate Toxicitymentioning
confidence: 99%